Human-Induced Hydrological Connectivity: Impacts of Footpaths on Beach Wrack Transport in a Frequently Visited Baltic Coastal Wetland - Karstens, Svenja; Kiesel, Joshua; Petersen, Lennart; Etter, Kilian; Schneider von Deimling, Jens; Vafeidis, Athanasios T.; Gross, Felix (Frontiers in Marine Science, 2022)
Coastal wetlands depend on vertical accretion to keep up with sea level rise in cases where embankment restricts accommodation space and landward migration. For coastal wetland survival, autogenic productivity (litter, root decay) as well as allogenic matter input are crucial. Beach wrack composed of seagrass and algae can serve as an important allogenic matter source, increases surface roughness, elevates the backshore and influences the blue carbon budget. The objective of this study is to understand how human footpaths in a frequently accessed Baltic coastal wetland influence beach wrack transport and accumulation. Beach wrack monitoring during the winter storm season 2021/2022 was conducted in high spatial and temporal resolution with bi-weekly UAV flights. Object-based identification, segmentation and classification of orthophotos with open-source software allowed the detection of beach wrack patches with a mean area of 0.6-2.7 m². Three major storm events occurred during the monitoring period (Arwen, Malik, Eunice). Regardless of wind speed or direction, the main accumulation zones remained stable. The east-west footpath that crosses the coastal wetland and connects the tourist hotspots served as a ‘highway’ for water-mediated transport of beach wrack. Total area covered by beach wrack fluctuated between 1793-2378 m² with a peak after storm Malik in January 2022. The densely accumulated beach wrack along the main east-west footpath formed an elongated micro-cliff-like structure and limited landward transport. Additional aerial image analysis for the last fifteen years showed that the position of the footpaths remained stable. This pioneering study offers first insights into the fate of beach wrack in an anthropogenically influenced Baltic coastal wetland where larger tidal channels that usually generate hydrological connectivity are missing. The identified transport patterns and accumulation hotspots are a starting point for further research on how beach wrack behaves in (waterlogged) coastal wetlands compared to decomposition on sandy beaches.